MENGUKUR EFEKTIFITAS PROSES PEMBELAJARAN DISCOVERY LEARNING PADA POKOK BAHASAN USAHA DAN ENERGI - Ade Putri (UIN Sunan Gunung Djati Bandung, 2017)
Physics learning in Vocational High School is considered ineffective, this is due to the lack of media and teaching materials during the learning activities. In addition, the ability of teachers to use the same methods and models, asking for learning in the classroom becomes monotonous and increases the knowledge and skills of students. The purpose of this research is to measure the effectiveness of learning with the Discovery Learning model on work and energy material through the AABTLT with SAS assessment system. The method used is descriptive method. The research was conducted at the Muhammadiyah 2 Cibiru Vocational School, with the sample of the study being 41 students from class X RPL. The results of the study show that there is a relationship between learning design that has been prepared with the achievement of learning by students. This research concludes that the use of the Discovery Learning model can measure the effectiveness of learning which shows the average achievement of each step of the activity exceeds 50%, where in the preliminary activities reached 82.14%, essences activities 71.83% and closing activities 61.31%